PEMARASAN POLITIK PARTAI DEMOKRASI INDONESIA PERJUANGAN PADA PILKADA SURABAYA 2015 (Studi Kasus Pemenangan Pasangan Risma – Whisnu) - Veranus Sidharta (MediaKom : Jurnal Ilmiah Komunikasi, 2017)
The elections of Surabaya, held on December 9, 2015, to elect Candidate Mayor and Candidate Deputy Mayor period 2015 - 2020, followed by two candidate pairs, candidate pair No. 1 (Rasiyo - Lucy) and candidate pair No. 2 (Risma - Whisnu). Where in the elections the couple Risma - Whisnu won a landslide victory over the couple Rasiyo Lucy with a valid vote acquisition of 86, 34%. Victory of Risma Whisnu Couple is interesting to be studied, therefore the writer did this research to know the strategy used by PDI-P party and the winning team of Tri Rismaharini and Whisnu Sakti Buana pair in Surabaya 2015 election. The research methodology approach used is qualitative research with descriptive research design. Data analysis techniques in this study using interactive model analysis techniques from Huberman and Miles. Data collection techniques use observation, interview and documentation. Informant amounted to 3 people from Risma-Whisnu winning team. In the implementation of Pilkada the party bearers and successful teams using political marketing called the marketing mix or Marketing mix 4P which includes four elements namely, product, price, place, promotion. The results of this study indicate that the strategy undertaken by the PDI-P party and the successful team is by directly lowering its candidate Risma-Whisnu to campaign directly to the residents in two-way communication and to absorb the aspirations of the people.